Indonesia Agroindustry Growth Acceleration through Export Tax Policy: CGE Comparative Static Model - Agusalim, Lestari (Jurnal Ekonomi Kuantitatif Terapan, 2017)
The purpose of this research is to analyze wether export tax policy on primary agriculture commodity can stimulate the growth of agroindustry. The model used in this research is a comparative static CGE model. The data used is the Input-Output Table in 2008, the System Accounting Matrix (SAM) Table in 2008, and other relevant supporting sources. Simulations carried out by applying export taxes on primary agricultural commodities, adjusted by government policy to accelerate the growth of agroindustry. The simulation indicates that it can inhibit the export growth on taxed commodities so that accelerate the long term agroindustrial output growth. Although it has negative effect on the short term. On the other hand, the policy doesn’t pro the economic growth and aggravate the export competitiveness.
Keywords: agroindustry, export tax, GDP, CGE